Nilai Sosial dan Moralitas dalam Naskah Drama Janji Senja Karya Taofan Nalisaputra - Agung Nugroho (LP4MK STKIP PGRI Lubuklinggau, 2018)
The purpose of this study was to describe the social values and moral values of drama scripts. The drama manuscript used was titled Janji Senja by Taofan Nalisaputra. This study used descriptive qualitative method. The results of this study are a description of the study of social values and moral values of the drama drama Janji Senja by Taofan Nalisaputra. The results of the social value study that dominates the drama script Janji Senja by Taofan Nalisaputra namely the social value of self with others this is seen from the quote